Analisis Maqāṣid al-Syarī‘ah terhadap Laki-Laki yang Meninggalkan Salat Jumat karena Menjaga Keamanan Kendaraan Jamaah: Studi Kasus di Masjid Wilayah Kota Medan - Ghiffari, Ahmad Fadhli Al; Syam, Syafruddin (AL-SULTHANIYAH, 2026)
Friday prayer is obligatory for adult Muslim men; however, in several major mosques in the city of Medan, security personnel are unable to perform it because they are assigned to guard the congregants’ vehicles. This study aims to analyze the legal status of this practice within the framework of the objectives of Islamic law. The research employs a qualitative method with a case study at three mosques in Medan, using observation, interviews with security personnel, mosque administrators, and religious figures, as well as normative analysis based on fiqh and Maqasid al-Shariah. The findings indicate that the duty of guarding vehicles may constitute a valid legal excuse (‘udhr shar‘i) when it concerns public welfare, when no effective substitute is available, and when there is a real potential for harm if the duty is neglected. These findings affirm the relevance of contemporary social practices to the principles of Maqasid al-Shariah in the protection of property (ḥifẓ al-māl) and, in certain circumstances, the protection of life (ḥifẓ al-nafs), while also highlighting the need for structured mosque management.